(untitled) (Global Journal of Human-Social Science, 2023)
It seems that the modernity with which Arab societies were shaped was completely devoid of philosophy and methodology and tribalism and sexual racism remained a major component in shaping the psychology of the Arab self After the necessary distinction between Islam as a culture and fundamentalism as a political ideology I would like to talk in this paper about the complete marginalization of the role of women in politics Where do women sit in Islamic political history And if they have a place why are they marginalized This research paper aims to shed light on the political position of women in Islam